Equações volumétricas e de afilamento para mogno africano (Khaya ivorensis A. Chev.) nos Estados de Minas Gerais e Pará, Brasil - Oliveira, Ximena Mendes de (2017)
Khaya ivorensis (African mahogany) yields high-quality and high-priced wood at the international market. Planting area is in expansion in Brazil and information is need to enhance planing and optimization of the forest activities. This motivated this dissertation and two papers were produced: the first tests single and double-entry models to fit commercial and total volume for Khaya ivorensis stands at first thinning (7 years) and final cut ages (14 – 15 years); and in the second paper polynomial non-segmented models were fitted to estimate diameters and volume at different positions the tree up to the commercial height. Taper was calculated up to 6 meters and the tree was assorted by different products. It was used 2 data bases: 100 trees with age close to the first thinning (from a Minas Gerais plantation) and 46 trees with ages close to final cut (from a Pará plantation). Tree volume was measured indirectly using Criterion RD 1000. Indirect measurements were validated comparing values obtained directly from 10 felled trees, being diameters and volumes from direct and indirect measurements statistically equal (α=0,05). Volume was calculated using Smalian’s formula. On the first paper, double-entry equations overperformed single-entry equations and Schumacher and Hall model was selected to estimate commercial volume for plantations with age close to the first thinning and final cut. Spurr Logarithmized model was the best to estimate total volume of the plantation with age close to the first thinning and Spurr was the best to estimate total volume for the plantation with age close to final cut. On the second paper, older trees were more conical than the younger. Schöepfer, Hradetzky and Kozak polynomial models presented good fit and good precision statistics. Schöepfer was the most acurate for both studied ages. Information from this study was satisfactory and can be used to quantify Khaya ivorensis dendrometric values.